UPAYA GURU DALAM MENGATASI KESULITAN BELAJAR MATEMATIKA PADA KELAS III DI MI NU ROWOLAKU - Dini Riska Hapsari; Septiana Ramadhani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the mathematics learning difficulties of third-grade students at MI NU Rowolakuand the teacher's strategies in addressing them. Through a qualitative descriptive approach using observation, interviews, and documentation, it was found that students had difficulty reading and understanding story problems, distinguishing place value, and performing basic arithmetic operations. The main causes were low early literacy and a lack of learning support at home. The teacher addressed these problems using a scaffolding strategy through step-by-step explanations, individual guidance, the use of teaching aids, and remedial sessions. This strategy effectively helped improve students' understanding and learning independence.